Paroxetine Induced Akathisia: Necessity for Rational Use - Maryam Mousavi; Padideh Ghaeli; Fanak Fahimi (Research Center for Rational Use of Drugs (RCRUD), 2019)
Rare cases of akathisia have been reported with paroxetine in the literature. However, accurate diagnosis for early treatment is important since untreated akathisia can result in poor patient's compliance, treatment failure, aggressive or suicidal acts. We present a case of a 25-year- old female patient, suffering from akathisia, who was treated with paroxetine and olanzapine due to hypomania and general anxiety disorder. Our finding shows that side effects like akathisia could be addressed by the timing of the peak level of paroxetine. Thus, shifting the time of paroxetine consumption to reach its peak level at the sleeping period could be a rational approach for many patients.  More research is required to confirm that the observation of this case report was not accidental.